Indicadores ambientais de gastos na gestão de resíduos sólidos da área de saúde : HU/UFS - Lima, Adriana de (2011)
The users of accounting information needs related to environmental issues, information which involve the assets of the entity and its relationship with the environment. The new needs of users of accounting made to arise on Environmental Accounting, which, in recording technique and control of assets, may show the environmental costs that every entity carries. This work aims to develop additional financial statement that demonstrates the environmental costs related to waste health care, University Hospital, Federal University of Sergipe. Through analysis of the Waste Management Plan of Health Services to determine the suitability to current legislation, identifying environmental spending, ranking enabled or not, proposing a plan of accounts to include environmental accounting and the construction of indicators of sustainable management of waste from health services. In view of this, we carried out a survey on how many goals exploratory and descriptive procedures were used as case study, survey, bibliographic and documentary. The results showed that the waste management of health services at the University Hospital has unfavorable trend towards sustainability and that additional financial statement prepared by the Balance Sheet in its compensation framework demonstrated that during the period 2008 to 2010 spending environmental improvement, but compared to the equity of the UFS was a decrease in the value applied in the management of waste from health services. It is concluded that the study has created tools that allow the administration of the university hospital use them to monitor environmental costs and its suitability for the Waste Management Plan Health Services.